Experimental modeling of pressurized subglacial water flow: Implications for tunnel valley formation. Issue 11 (5th November 2016) - Lelandais, Thomas; Mourgues, Régis; Ravier, Édouard; Pochat, Stéphane; Strzerzynski, Pierre; Bourgeois, Olivier
Abstract: Tunnel valleys are elongated hollows commonly found in formerly glaciated areas and interpreted as resulting from subglacial meltwater erosion beneath ice sheets. Over the past two decades, the number of studies of terrestrial tunnel valleys has continuously increased, and their existence has been hypothesized also on Mars, but their formation mechanisms remain poorly understood. We introduce here an innovative experimental approach to examine erosion by circulation of pressurized meltwater within the substratum and at the ice/substratum interface. We used a permeable substratum (sand) partially covered by a viscous, impermeable, and transparent cap (silicon putty), below which we applied a central injection of pure water. Low water pressures led to groundwater circulation in the substratum only, while water pressures exceeding a threshold that is larger than the sum of the glaciostatic and lithostatic pressures led to additional water circulation and formation of drainage landforms at the cap/substratum interface. The formation of these drainage landforms was monitored through time, and their shapes were analyzed from digital elevation models obtained by stereo‐photogrammetry. The experimental landforms include valleys that are similar to natural tunnel valleys in their spatial organization and in a number of diagnostic morphological criteria, such as undulating longitudinal profiles and "tunnel" shapes. These results are consistent with the hypothesis that overpressurized subglacial water circulation controls the formation of tunnel valleys. Key Points: Subglacial tunnel valleys are reproduced experimentally by initiating pressurized water flow into a sandbox cover by a viscous cap Experimental valleys are similar in shape and spatial organization to natural tunnel valleys Experimental results demonstrate that overpressurized water flow is a controls the formation of tunnel valleys